Gestión escolar directiva como predictor del trabajo en equipo en docentes de centros de educación técnico productivas públicas Iquitos 2023 - Navarro Mejia, Dassi (2025)
The objective of this study was to determine directive school management as a predictor of teamwork in the public Technical-productive Education Centers of Iquitos in the year 2023. This is a predictive study with a field, contemporary, transversal, multivariate and ex-post-facto. A census sample of 90 people was included, divided between managers (06), hierarchical staff (06) and teachers (78). Questionnaires were used to measure research variables. Based on the overall results of the multiple linear regression model, a correlation of R= 0.730 was obtained, indicating a high and positive correlation. Likewise, the coefficient of determination R2 = 0.533, expressed as a percentage, is interpreted as a model that predicts 53.3% of teaching teamwork in the Technical-Productive Education Centers of Iquitos. The analysis of variance (ANOVA) of the components of the model with a significance of 0.000 shows that directive school management (strategic, administrative, pedagogical and community) predicts teamwork in the Technical-Productive Education Centers of Iquitos. These results obtained according to the multiple linear regression model allow us to conclude that school management predicts teamwork in the Technical-Productive Education Centers of Iquitos in 2023.